Sustained Groundwater Loss in California's Central Valley Exacerbated by Intense Drought Periods. Issue 7 (4th July 2018) - Ojha, Chandrakanta; Shirzaei, Manoochehr; Werth, Susanna; Argus, Donald F.; Farr, Tom G.
Abstract: The accelerated rate of decline in groundwater levels across California's Central Valley results from overdrafting and low rates of natural recharge and is exacerbated by droughts. The lack of observations with an adequate spatiotemporal resolution to constrain the evolution of groundwater resources poses severe challenges to water management efforts. Here we present SAR interferometric measurements of high‐resolution vertical land motion across the valley, revealing multiscale patterns of aquifer hydrogeological properties and groundwater storage change. Investigating the depletion and degradation of the aquifer‐system during 2007–2010, when the entire valley experienced a severe drought, we find that ~2% of total aquifer‐system storage was permanently lost, owing to irreversible compaction of the system. Over this period, the seasonal groundwater storage change amplitude of 10.11 ± 2.5 km 3 modulates a long‐term groundwater storage decline of 21.32 ± 7.2 km 3 . Estimates for subbasins show more complex patterns, most likely associated with local hydrogeology, recharge, demand, and underground flow. Presented measurements of aquifer‐system compaction provide a more complete understanding of groundwater dynamics and can potentially be used to improve water security. Key Points: Time‐dependent vertical land motion in California's Central Valley reflects the evolution of groundwater stocks during 2007–2010 Drought‐related dynamics of the aquifer‐system across the valley are investigated using deformation and groundwater level data Regional‐scale distribution of mechanical properties of the aquifer‐system is resolved.